Early Childhood Pre-Reading Literacy Skills Based On The Application Of Storytelling Methods - Rosita Dewi, Noer Azizah (BELIA: Early Childhood Education Papers, 2020)
Early childhood literacy is the ability to speak, read and write that children can naturally and can hone over time. Early reading literacy is a benchmark for parents in assessing children's intelligence, but early literacy skills can certainly be honed with learning activities. Storytelling is an activity to tell stories about a story that is conveyed to listeners. Storytelling has many benefits for children, and storytelling can be a fun activity for children. Children have learned many things without realizing it through storytelling.